Performance results of the improved working classification of superficial mycoses of the skin in carrying out their clinical and epidemiological monitoring - S. Akhmedova (Medičnì Perspektivi)
The results of testing of the improved working classification of superficial mycoses of the skin and its appendages (SMS) in the Republic of Azerbaijan for the period of 2012-2016 are presented. Given the variety of classifications of fungal skin diseases, many years of clinical experience have shown that none of them fully meets the requirements of a practicing physician. The author has developed and improved the classification of mycoses of the skin and its appendages, which will facilitate the diagnosis and the appointment of therapy, since this classification takes into account the tissue and topographic localization of the mycotic process, which greatly facilitates the diagnosis by dermatovenerologists, and will also reveal the true prevalence of mycotic pathology. Based on the traditional form No. 9, among 246 cases of superficial mycoses of the skin and its appendages identified in the city of Baku for the period of 2012-2016, the largest number of patients (79.44±2.6%) were diagnosed with mycoses of the scalp – 32, 52±1.21%, smooth skin mycoses – 30.08%±1.28 multi-colored lichen – 14.80%±1.01, which corresponds to the frequency of occurrence of these forms of SMS at the age of 11-20 years (44.01±3,1%) and 0-10 years (39.08±3.1%), leaders in the age line of groups with SMS in Baku. A reliable statistical difference was revealed in the detection of superficial mycoses of the skin and its appendages in the city of Baku during the study period. Based on the developed working classification, the nosological structure of the incidence of SMS in the city of Baku for the period 2012-2016 is represented by the following – 1919 episodes: mycoses of the scalp – 675 patients (35.17±1.1%); mycoses of smooth skin – 638 patients (33.25±1.1%); multi-colored lichen – 264 patients (13.76±0.8%); combined mycoses of smooth skin and scalp – 134 patients (6.98±0.6%); onychomycoses – 97 patients (5.05±0.5%); purulent-infiltrative form of mycoses – 66 patients (3.44±0.4%); skin candidiasis – 19 patients (0.99±0.2%); feet of the mycoses – 19 patients (0.99±0.2%); inguinal epidermophytosis – 7 patients (0.36±0.1%). The prevalence of nosologies preserved in the largest number of patients (1578 patients – 82.23±0.9%), mycoses of the scalp – 35.17±1.1% (675 patients), smooth skin mycoses – 33.25±1.1% (638 patients), multicolored lichen – 13.76%±0.8 (264 patients). The greatest number of patients with SMS was also detected in the age group of 11-20 years (42.12±3.1%) and 0-10 years (40.32±3.1%). The data of a comparative analysis of the results of the developed and improved classification of superficial mycoses of the skin and its appendages with the data of the traditional reporting form, made it possible to expand the scope of the analyzed nosologies and increase the objectivity of statistical data for assessing the epidemiological situation in the study region.